Separation of bio‐based chemicals using pervaporation. Issue 9 (8th May 2020) - Li, Wenqi; Estager, Julien; Monbaliu, Jean‐Christophe M; Debecker, Damien P; Luis, Patricia
Abstract: The increasing demand of raw materials and the ever‐present risk of fossil resource depletion are effective motivators for the development of new bio‐based routes for the synthesis of chemicals. The use of non‐renewable natural resources, such as fossil fuels, and the generation of greenhouse gases have led to severe environmental problems. However, one of the challenges of using renewable biomass resources to produce building block molecules is achieving an efficient and economically viable purification step. The complexity of the mixture involves generally high separation costs. Separation processes, such as distillation and liquid–liquid extraction, have been proposed to purify target bio‐based compounds. However, the high energetic cost associated with such processes is pushing the current research towards the development of alternative solutions. In this context, membrane technology, such as pervaporation, is an interesting solution for minimizing the energy consumption of the process. This review highlights the main parameters and factors that impact the performance of pervaporation in the separation of complex bio‐based chemical mixtures. Coupling effects, which are among the critical issues in pervaporation, are discussed in detail. Hybrid processes, in which both reaction and distillation are performed during the pervaporation process, are also addressed. © 2020 Society of Chemical Industry